2020
DOI: 10.21307/ane-2020-026
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of hepcidin and interleukin 6 in Parkinson’s disease

Abstract: Neurodegeneration in Parkinson's disease (PD) includes processes of chronic inflammation and oxidative stress which are related to dysregulation in the homeostasis of iron metabolism. Hepcidin is a peptide hormone responsible for systemic iron homeostasis and simultaneously the inflammatory response protein, induced in response to interleukin 6 (IL-6). We assessed the serum concentration of hepcidin and IL-6 in the groups of patients with PD treated only pharmacologically with optimal individualized therapy (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…We performed a screening of the abstracts of all original articles, and publications in abstract form were excluded from further analysis. The initial selection included 76 studies measuring CSF, serum/plasma or urine levels of iron, ferritin, transferrin, lactoferrin, haptoglobin, and or hepcidine [6,9–83]. Table 2 summarizes the methods used for the determinations, the main results, and observations in some of these studies, including the reason for exclusion of several of these studies from the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We performed a screening of the abstracts of all original articles, and publications in abstract form were excluded from further analysis. The initial selection included 76 studies measuring CSF, serum/plasma or urine levels of iron, ferritin, transferrin, lactoferrin, haptoglobin, and or hepcidine [6,9–83]. Table 2 summarizes the methods used for the determinations, the main results, and observations in some of these studies, including the reason for exclusion of several of these studies from the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of other cytokines, acute phase response type 1 (including IL-1α, IL-1β, TNF-α and TNF-β), is indirect and requires more time after the activation of the inflammatory stimulus induces the secretion of IL-6, and it is only IL-6 that induces an increase in the production of hepcidin [ 192 ]. Kwiatek-Majkusiak et al showed that the serum concentrations of hepcidin and IL-6 in the group of all PD patients were significantly higher than in the control group [ 193 ]. Additionally, positive correlations between serum hepcidin and IL-6 were found in the PD group [ 193 ].…”
Section: Various Neurodegenerative Factorsmentioning
confidence: 99%
“…Kwiatek-Majkusiak et al showed that the serum concentrations of hepcidin and IL-6 in the group of all PD patients were significantly higher than in the control group [ 193 ]. Additionally, positive correlations between serum hepcidin and IL-6 were found in the PD group [ 193 ].…”
Section: Various Neurodegenerative Factorsmentioning
confidence: 99%
“…Activation of systemic inflammatory responses via an acute increase in proinflammatory cytokines, including interleukin-6 (IL-6) termed as Cytokine Storm, has been linked to disease severity and death in COVID-19 patients (Hashizume, 2020;Hojyo et al, 2020;Lukan, 2020). IL-6 like pro-inflammatory interleukins are also elevated in some neurodegenerative diseases such as Parkinson's disease (PD) (Kwiatek-Majkusiak et al, 2020), suggesting that patients with neurodegenerative diseases may be more susceptible to the severity of COVID-19. Although the relationship between COVID-19 severity and the progression of neurodegeneration diseases is not yet established, studies have shown that the COVID-19-related mortality rate is significantly higher in PD patients (Fasano et al, 2020;Zhang et al, 2020).…”
Section: Neurological Manifestations In Coronavirus Disease 2019mentioning
confidence: 99%
“…Edema and neuronal degeneration and the presence of SARS CoV particles or the viral genomic sequences together with circulating immune cells in different brain parts were identified in SARS-CoV infected patients ( Gu et al, 2005 ). Several studies related the SARS CoV infection in patients with late-stage SARS with neuronal and psychologic abnormalities ( Chan et al, 2006 ; Yip et al, 2010 ). Similar neurological observations, including encephalitis, infectious and toxic neuropathies, and Guillain-Barré syndrome, were found in coronavirus MERS-CoV infected patients ( Kim et al, 2017 ).…”
Section: Neurological Manifestations In Coronavirus Disease 2019mentioning
confidence: 99%